The Optimum Conditions of Fire Tube Boiler fuelled with - Leily Nurul Komariah (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
A various tests of biodiesel use in any combustion facility were conducted in order to comply the government mandatory regarding stages of biodiesel utilization, especially in industrial and commercial sectors. The higher biodiesel blends that applied in the boiler show a significant effect on emissions reduction but followed by a reduction in boiler efficiency and an increase in fuel consumption. This study was carried out using palm oil-based biodiesel in the fire tube boiler with 3 bar operating pressure and heat input of 60,000 kcal/hour. In this study, an adjustment scale of the fan damper is conducted in order to control the amount of excess air that enters the combustion chamber. This study showed that the more percentage of biodiesel in fuel blends, the amount of combustion air must reduced. This mechanism was effective through fine-tuning of the fan damper scale. This adjustment may result an increase in efficiency of 0.64 to 2.6%.